The Construction of Computer-aided Translation Teaching Platform Based on Corpus. Issue 3 (October 2020) - Gao, Tingting; Wang, Xiaoyi
Abstract: Corpus provides the translator with a set of possible translation units or equivalent texts in different languages, so that learners have the opportunity to bring questions to the real corpus to find answers. Through observation and analysis, this paper sums up meaningful translation strategies, improves translators' awareness of dealing with translation difficulties and using translation strategies, and learns to evaluate or reflect on their own translation behaviors. Using corpus to study the cultivation of translators can help future translators to be familiar with the characteristics of translation profession, improve their autonomy and flexibility, and be ready to undertake real translation tasks in the future. The greatest educational value of using corpus to train translators lies in arousing the translator's thinking rather than merely providing ready-made answers. In order to promote the rapid growth of qualified translators, it is imperative to reform the course system of college translation, carry out the research of students' translation texts, and build the corpus of learners' translation.